Who says what is absurd? A case study on being(s) in an alternative normality - Corinna Burkhart (Vereinigung für Ökologische Ökonomie, 2015)
This thesis deals with norms and the perception of possibilities. I discuss how norms, individuals and society are interlinked and interdependent. From this basic connection, based on the case of Can Decreix, a centre for practical and theoretical experiments on the topic of degrowth, I explore how a different normality can be established. The way that norms both enable and restrict is discussed and used to explain Can Decreix's internal dynamics as well as those with the surrounding growth society. The study focuses on experiences made by individuals who spent time within the different normality of Can Decreix. Methods used to integrate the case and individual experiences are participant observation, semi-structured interviews and the analysis of my own experiences. Based on these materials I discuss how the individual's subjectivities are influenced by experiences in Can Decreix. One consequence of these cross-normality experiences is what I call a defamiliarization of the subjects. Having identified norms as powerful, partly because of naturalization, I discuss what practical defamiliarization can mean in the context of social change.
urn:nbn:de:101:1-201704231360
Keywords: D01; 330; normality; degrowth; Can Decreix